Identification and Validation of Reference Genes for Gene Expression Analysis in Monochamus saltuarius Under Bursaphelenchus xylophilus Treatment - Li, Jiaxing; Fu, Ningning; Ren, Lili; Luo, Youqing (Frontiers in Physiology, 2022)
A special mutual relationship exists between the pine wood nematode (PWN) Bursaphelenchus xylophilus and its vector beetles of genus Monochamus, which enables PWN to spread, at the same time provides longhorned beetles with more weak hosts. PWN are attracted to the pupal chambers and then carried inside the trachea of beetle adults, which is a necessary part to complete the B. xylophilus infection cycle. The growth and immune responses of the vector beetle will affect this carrying process, however, they were rarely studied in Monochamus saltuarius. Real-time quantitative polymerase chain reaction (RT-qPCR), one of the most common methods for quantitative gene expression analysis, was performed to explore the key genes and pathways involved in the growth, development and immune responses of M. saltuarius at different developmental stages associated with infection of PWN and PWN treatment conditions. To enhance the accuracy of RT-qPCR data, the expression of target genes needs to be normalized with reference genes, which are stably expressed under varied experimental conditions. In our study, the stability of 14 candidate reference genes in M. saltuarius samples at different developmental stages associated with infection of PWN or PWN treatment conditions was evaluated using delta Ct, geNorm, NormFinder, BestKeeper and RefFinder algorithms. Moreover, KLF gene was used to validate the stability of the selected reference genes. Under experimental conditions of this study, RPL7 and TER were suitable reference genes at different developmental stages associated with infection of PWN. RPL7 and RPS5 were considered the most stable reference genes in the pupae treated with PWN. RPS5 and SNX6 could be used as reference genes in the adults treated with PWN. RPL7, EF1-γ, and RPS5 could be used as stable reference genes in all the samples. This work is the first to evaluate reference genes in M. saltuarius, laying a foundation for further gene expression experimental procedures and understanding the phoretic relationship between M. saltuarius and B. xylophilus.